(untitled) (Raparin Journal of Humanities (RJH), 2022)
This study is an attempt to clarify translation between mother tongue and foreign languages; it means the translations between two different languages. The contents consist of (introduction, idiomatic translation, proverbial translation, literary translation, and the terms that untranslatable). In literary translation we choose the poetry for two reason, firstly its main topic of literary translation, secondly its difficult topic translation. This study tries to show the difficulties and obstacles of each of these subjects, because each of them has a set of cultural and social characteristics, and they have a direct and complete relationship with human emotions and feelings. We mean choosing this title is human genitals will be a competence and any languages other than this language will be a performance for it, and also competence and performance will form an important part of all the languages of the world, because the competence is the basis of the creation of language, and performance is the expression of the language, and this caused choosing the subject and mixing with translation.